PHARMACOLOGICAL ACTIVITY OF ULVA LACTUCA POLYPHENOLS FRACTION: CARDIOPROTECTIVE AND ANTIOXIDANT ACTIVITIES AGAINST ISOPROTERENOL-INDUCED MYOCARDIAL INFARCTION IN RATS - RAVINDRAN NT; MOHAMED SADIQ A (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study is to assess the activity of Ulva lactuca polyphenols fraction in protecting the myocardial infarction induced by a high dose of isoproterenol. Methods: This study was carried out using Wistar albino rats divided into six groups. Group 1 was the normal group. Groups 2, 3, 4, 5, and 6 received isoproterenol (85 mg/kg) i.p. twice at an interval of 24 h on the 14th and 15th day. In addition to isoproterenol, Group 3 received verapamil (5 μmol/kg) as a single dose intravenously on the 14th day 10 min before isoproterenol and Groups 4, 5, and 6 received U. lactuca polyphenols fraction at the doses of 50, 100, and 200 mg/kg, respectively, for 14 days. On the 16th day, serum and heart samples were harvested from the animals and the cardioprotective and antioxidant activities were assessed by studying the levels of cardiac functional heart marker enzymes, lipid profile, reduced glutathione, and antioxidant enzymes. Results: U. lactuca polyphenols fraction, at the tested doses, restored the levels of all serum markers and enzymes (aspartate aminotransferase, alanine aminotransferase, creatine phosphokinase, lactate dehydrogenase, cholesterol, triglycerides, and reduced glutathione) and heart homogenate antioxidant markers (reduced glutathione, superoxide dismutase, catalase, and glutathione peroxidase) significantly, in dose-dependent manner. Conclusion: This study suggests that U. lactuca polyphenols fraction has a cardioprotective effect against isoproterenol-induced myocardial infarction and possess antioxidant activities.